2001
DOI: 10.1142/s0217979201002540
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall Resistivity Based on a Linear Response Theory

Abstract: The resistivity due to a domain wall in a ferromagnetic metal is calculated based on a linear response theory. The scattering by impurities is taken into account. The electronwall interaction is derived from the exchange interaction between the conduction electron and the magnetization by use of a local gauge transformation in the spin space. This interaction is treated perturbatively to the second order. The classical (Boltzmann) contribution from the wall scattering turns out to be negligiblly small if the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
(97 reference statements)
1
15
0
Order By: Relevance
“…Due to the strong shape anisotropy, for these wires the magnetization is everywhere oriented within the wire plane, but one might argue that the local variation of the magnetization within Néel-type domain walls would lead to a reduction of WEL effects even in zero magnetic field. 35 However, even for the cobalt wire with a width of 440 nm, which is in a single-domain-like remanent state and can be considered two-dimensional, the respective magnetic field dependence of ⌬G͑10͒ is found to be almost identical as compared to the wire with a width of 5.2 m ͑see Fig. 3͒.…”
Section: Temperature Dependencementioning
confidence: 93%
“…Due to the strong shape anisotropy, for these wires the magnetization is everywhere oriented within the wire plane, but one might argue that the local variation of the magnetization within Néel-type domain walls would lead to a reduction of WEL effects even in zero magnetic field. 35 However, even for the cobalt wire with a width of 440 nm, which is in a single-domain-like remanent state and can be considered two-dimensional, the respective magnetic field dependence of ⌬G͑10͒ is found to be almost identical as compared to the wire with a width of 5.2 m ͑see Fig. 3͒.…”
Section: Temperature Dependencementioning
confidence: 93%
“…The theory presented here completely neglects impurity scattering except in the most crude approximation of diffusive transport. Existing work on the problem for domain wall transport is very limited, but the results by Tatara [12] for strong scattering centers illustrates some of the interesting possibilities. Tatara showed that a domain wall may suppress weak localization in the case of very strong scattering, and additional numerical calculations for weak and moderate scattering potentials appear to support this conclusion.…”
Section: Spin Dependent Transportmentioning
confidence: 99%
“…On the other hand for the current-induced case, when an electron passes through a magnetic DW, it will be scattered by the noncollinear magnetic structure, which results in the phenomenon of magnetoresistance (MR). 22 Meanwhile, the conduction electron can also transfer the spin angular momentum to the local spin when it flows through the DW. So a spin-transfer torque will exert on the local magnetic moment and then the electric current can be used to manipulate the magnetic structure of DW.…”
Section: Introductionmentioning
confidence: 99%